2012
DOI: 10.1038/cgt.2012.70
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases-3 transfer suppresses malignant behaviors of colorectal cancer cells

Abstract: Colorectal carcinoma is one of the most frequent cancer diseases. For patients with this type of cancer, liver metastases are the main cause of death. Therefore, new therapeutic approaches are urgently needed to improve the outcomes. We found that both mRNA and protein levels of tissue inhibitor of metalloproteinase-3 (TIMP3) were decreased significantly in colorectal cancer tissue when compared with normal mucosa, suggesting that decrease of TIMP3 expression was correlated with malignant behavior of colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…TIMP3 is a member of tissue inhibitors of metalloproteinases (TIMP), which are the key inhibitors of MMPs [17]. Down-regulated TIMP3 was observed in many malignant tumors including colorectal cancer [21][22][23]. Although hypermethylation of the TIMP3 gene promoter may contribute to silencing of the TIMP3 gene expression [22], the present study suggests miR-191-mediated gene inhibition is an alternative regulatory mechanism.…”
Section: Discussionmentioning
confidence: 80%
“…TIMP3 is a member of tissue inhibitors of metalloproteinases (TIMP), which are the key inhibitors of MMPs [17]. Down-regulated TIMP3 was observed in many malignant tumors including colorectal cancer [21][22][23]. Although hypermethylation of the TIMP3 gene promoter may contribute to silencing of the TIMP3 gene expression [22], the present study suggests miR-191-mediated gene inhibition is an alternative regulatory mechanism.…”
Section: Discussionmentioning
confidence: 80%
“…However, it is now appreciated that the activities of TIMPs are not restricted to MMP inhibition alone. To date, activities of TIMP3 known to be independent of metalloproteinase inhibition include induction of apoptosis in a number of cancer cell lines [22][23][24] and the inhibition of angiogenesis [21]. Most interestingly, we found that intravenous (IV) delivery of recombinant TIMP3 could recapitulate in part the beneficial effects of MSCs on the BBB [19].…”
Section: Introductionmentioning
confidence: 83%
“…6A) suggests that mTORC1 inhibition with rapamycin would inhibit the preservation/reinnervation of neuronal projections (b3-tubulin staining) whereas Akt inhibition with triciribine would inhibit the preservation/reinnervation of neuronal projections but would also attenuate the survival of mature neurons (NeuN staining) and neuronal stem cells (DCX staining). To address these hypotheses, we repeated our TBI 1 TIMP3 experiments with three IV injections of 60 lg/kg TIMP3 as before (1,24, and 72 hours post-TBI) but modified the design to include intraperitoneal injections of either 1 mg/kg triciribine or 1 mg/kg rapamycin 30 minutes prior to each IV TIMP3 delivery. As before, animals were sacrificed 7 days post-TBI in order to compare with our findings in Figures 1 and 5.…”
Section: Pharmacological Inhibition Of Mtor and Akt Differentially Sumentioning
confidence: 99%
“…In a study examining the use of TIMP-3 as biotherapy for CRC, adenovirus-mediated TIMP-3 transduction arrested cancer cell growth and induced apoptosis. In vitro data also revealed that increasing TIMP-3 levels reduced adhesion, migration and invasiveness of a human colon cancer cell line, while in vivo studies revealed that TIMP-3 transduction reduces both tumor growth and liver metastasis [43]. …”
Section: Tissue Inhibitors Of Metalloproteinasesmentioning
confidence: 99%